Inventory of water storage types in the Blue Nile and Volta River Basins - Johnston, Robyn M.; McCartney, Matthew P. (International Water Management Institute, 2010)
For agriculture there is a continuum of water storage options, ranging from groundwater aquifers, soil water, natural wetlands and small ponds and tanks to large reservoirs. In any situation each of these has its own niche in terms of technical feasibility, socioeconomic sustainability and impact on public health and the environment. Planning storage requires insight into impending needs and also a good understanding of what already exists and what was, and was not, successful, in the past. This report provides an inventory of existing and prospective water storage in the Ghanaian Volta and the Ethiopian Blue Nile basins. It provides as much quantitative data as possible, but highlights both the dearth of readily available information and the lack of integrated planning of storage in both basins. Recommendations are made for improved planning in the future.